2021
DOI: 10.3389/fnins.2021.756868
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Spectrum Disorder Detection and Structural Biomarker Identification Using Self-Attention Model and Individual-Level Morphological Covariance Brain Networks

Abstract: Autism spectrum disorder (ASD) is a range of neurodevelopmental disorders, which brings enormous burdens to the families of patients and society. However, due to the lack of representation of variance for diseases and the absence of biomarkers for diagnosis, the early detection and intervention of ASD are remarkably challenging. In this study, we proposed a self-attention deep learning framework based on the transformer model on structural MR images from the ABIDE consortium to classify ASD patients from norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…Liloia et al (2021) found middle occipital gyrus in GM co-alteration network of ASD [ 53 ]. Wang et al (2021) used the deep learning method and structural covariance network to classify ASD and found salient ROIs in prefrontal regions [ 54 ]. In our experiment, each layer had salient ROIs from the visual network associated with ASD, and more ROIs of the frontoparietal control network became more significant with the depth of layers.…”
Section: Discussionmentioning
confidence: 99%
“…Liloia et al (2021) found middle occipital gyrus in GM co-alteration network of ASD [ 53 ]. Wang et al (2021) used the deep learning method and structural covariance network to classify ASD and found salient ROIs in prefrontal regions [ 54 ]. In our experiment, each layer had salient ROIs from the visual network associated with ASD, and more ROIs of the frontoparietal control network became more significant with the depth of layers.…”
Section: Discussionmentioning
confidence: 99%
“…Grad-CAM heat maps are hierarchical, like CNN's simpleto-complex feature extraction algorithm (Gao et al, 2022). However, in Wang et al (2021), the maps of self-attention coefficients in the first and second layers are similar, indicating a consistent diagnosis. In Leming et al (2021), the authors verified their suggested approach for classifying individuals with ASD and age-, motion-, and intracranial-volume-matched HCs by feeding a CNN the symmetric similarity matrix from regional histograms of estimated GM volumes.…”
Section: Deep Learning-based Autism Spectrum Disorder Classification ...mentioning
confidence: 99%
“…The F1 score is calculated by averaging the PPV and Sen scores. Therefore, this score takes both FP and FN into account ( Panja et al, 2018 ; Wang et al, 2021 ).…”
Section: General Machine Learning Pipeline and Common Algorithms For ...mentioning
confidence: 99%
See 2 more Smart Citations